(untitled) (Journal of Student Affairs in Africa, 2021)
There is a great deal of variability in the practice of orientation across the country at South Africa’s universities, and there is limited knowledge of what exactly constitutes good practice in orientation. Many areas of enquiry remain unexplored, and remain blind spots for South Africa’s higher education sector. The article addresses this central question: What constitutes good practice for orientation programmes in South Africa? The article argues that a structured and informed orientation strategy is critical in terms of matters of student retention and, in fact, may serve as the key linchpin of students’ decision to stay or exit the higher education system. Accordingly, seven strategies to improve nationalorientation practice are proposed in this article.